2019
DOI: 10.1101/518514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Signal integration and information transfer in an allosterically regulated network

Abstract: 10A biological reaction network may serve multiple purposes, processing more than one input and impacting downstream processes via more than one output. These networks operate in a dynamic cellular environment in which the levels of network components may change within cells and across cells. Recent evidence suggests that protein concentration variability could explain cell fate decisions. However, systems with multiple inputs, multiple outputs, and changing input concentrations have not been studied in detail… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Other forms of coupling are possible with enzymatic modifications. For example, a single enzyme can effect modifications on multiple substrates allowing for a sophisticated degree of cross talk and coupling between pathways [45,46,47,48]. We studied the propensity for biphasic responses in the system with enzyme sharing between two covalent modification cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Other forms of coupling are possible with enzymatic modifications. For example, a single enzyme can effect modifications on multiple substrates allowing for a sophisticated degree of cross talk and coupling between pathways [45,46,47,48]. We studied the propensity for biphasic responses in the system with enzyme sharing between two covalent modification cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the transfer of information in biochemical networks by entropy-based methods pointed to the particular importance of noise (Cheong et al, 2011;Shockley et al, 2019;Suderman et al, 2017). In particular, Suderman et al (2017) investigated information transfer at the single-cell and the cell-population level.…”
Section: Discussionmentioning
confidence: 99%
“…Seminal works in the field have shown that the maximum channel capacity of a biochemical process is context dependent and could require the cooperativity of multiple cells to achieve actual information transfer 21 . In recent work, our laboratory showed a non-linear dependence between channel capacity and reaction flux through a network 22 . Despite these advances to explore network-driven processes, a truly systems-level interpretation of non-equilibrium dynamics in a network and how these transient dynamics are impacted by parameter uncertainty remains a standing challenge in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple approaches have been used to extract mechanistic insights from mathematical models of network-driven processes. These approaches range from simple tracking of one or multiple species in the network [14][15][16][17][18] to more complex applications, such as Information Theoretic concepts to estimate the channel capacity between nodes in a network [19][20][21][22] . The latter approaches have provided a quantitative paradigm to study input/output relationships in networks [20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation